Challenges And Opportunities For Islamic Education In The Digital Age - Mubiarto, Akhli Nur (Jurnal Multidisiplin, 2024)
The advancement of digital technology has brought significant changes to various sectors, including education. In the context of Islamic education, the digital era presents both challenges and opportunities. The shift towards digital platforms has transformed traditional methods of learning and teaching, offering greater accessibility to educational resources. However, this transformation also brings about challenges such as the digital divide, the need for digital literacy among educators and students, and the potential erosion of moral values. This article explores both the challenges and opportunities of Islamic education in the digital age, with a focus on the ways educators can adapt to technological advancements while maintaining the core values of Islamic teachings. The study also discusses the role of digital tools in enhancing the delivery of Islamic knowledge, as well as the importance of integrating digital literacy within Islamic educational institutions.